SPECIFIC FEATURES OF THE TAX DEBT COLLECTION MECHANISM IN THE TAX ADMINISTRATION IN DIGITAL DEVELOPMENT (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In the context of the development of the digital infrastructure, the specific features of the tax debt collection mechanism in the tax administration were studied in this article, the main focus is on the role of tax legislation and the obligations of taxpayers. Also, conclusions were drawn on general problems, including the need to improve the enforcement of tax obligations and tax evasion, and the need to make tax legislation and tax rules more precise and simpler. At the same time, some important reforms were studied and scientific-practical conclusions and proposals were developed on foreign experience and its application in our country.